Sistem Pangkalan Data Akademik (PDA) (Studi Kasus : Lembaga Pendidikan SMPIT Insan Madani) - Yus Jayusman; Mochammad Farhan (LPPM STMIK Bandung, 2021)
Computer technology plays a very important role for developments in all fields. One of the fields is data processing technology. The rapid development of technology has influenced various fields, one of which is education. One of the results of teaching and learning activities is in the form of data, both qualitative and quantitative data. The results of this data processing are the spearhead of measuring the success of students in following a lesson and determining the real direction of student learning. However, currently most of the data processing in educational institutions, especially in SMPIT Insan Madani, still uses conventional methods, namely not using a computerized system, this of course causes vulnerability to data loss and damage, besides that the data will accumulate and make it difficult if at any time the data is needed. back. For this reason, the authors designed an application in the form of an Academic Database (AD) that can be used by schools to help process data that was previously manual into a computerized system.